Regional economies - The ILCA programme countries - East Africa: Ethiopia and Kenya - International Livestock Centre for Africa (1978)
Economic situation of the ILCA programme countries, particularly agricultural production, animal production and comparative analysis of price indicators in Ethiopia and Kenya.